The Relationship Between Macronutrients Intake And Physical Activity With Nutritional Status Of Nutrition Science Student At Muhammadiyah University of Surakarta - Idek Zahra Sabilla; Dyah Intan Puspitasari; Elida Soviana (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Indonesia currently faces a triple burden of nutritional problems including stunting, wasting and obesity,and deficiency in micronutrients such as anemia. Nutritional problems still commonly found among adolescents and adults include undernutrition, overnutrition, and anemia. These nutritional problems are influenced from several factors including food intake, physical activity, socio-cultural, economic, and nutritional knowledge. The aims of this research was to examine the correlation between carbohydrate, fat, protein intake and physical activity with the nutritional status of nutrition science students at Muhammadiyah University of Surakarta. A cross-sectional method was used in this research involving 85 nutrition student respondents consisting of 20 thin respondents (23.5%), 62 normal respondents (72.9%), and 3 overweight respondents (3.5%). The study was conducted by providing a 24-hour recall form for 3 days, a PAL form for 7 days, and direct anthropometric measurements. The results showed no correlation between carbohydrate intake and nutritional status (p 0.217) indicating that H0 is accepted. The next results on this study found correlation between consumption of fat and nutritional status (p 0.049) which means that excessive fat intake can trigger obesity. Another result found no correlation between protein intake and nutritional status (p 0.470) nor between physical activity and nutritional status (p 0.228). Based on this research, it can be concluded that fat consumption is significantly associated with nutritional status. However, there is no significant associations were found for carbohydrate intake, protein intake, or physical activity with nutritional status of students.